Upaya Bhabinkamtibmas Dalam Mencegah Penyalahgunaan Minuman Keras Di Polres Tasikmalaya - Nofiandy, Muhammad Ryan (Indonesian Journal of Police Studies, 2020)
The inexorably far reaching use and circulation of mixed beverages is one of the issues that is generally disturbing for most Indonesians. This exploration was roused by the high course of liquor in the Tasikmalaya Police District, so that Tasikmalaya District gave a Regional Regulation No. 3 of 2014 concerning Peace and Public Order. Alcohol is one of the activating components of wrongdoing, for example, battling, burglary and misuse. Accordingly, this examination means to portray the flow of liquor in the lawful region of the Tasikmalaya Police Station, and how Bhabinkamtibmas' endeavors in forestalling the utilization of alcohol in the Tasikmalaya Regional Police and the variables that impact it. This investigation utilizes the Concept of Efforts, the Concept of Bhabinkamtibmas, the Concept of Preventing, the Concept of Liquor and furthermore the Theory of Preventing Crimes, Theory of Management. This investigation utilizes a subjective methodology, utilizes expressive expository exploration strategies, and examination information is gathered through meetings, perceptions and archive survey. The outcomes indicated that the flow of liquor in the lawful region of ​​the Tasikmalaya police headquarters was as yet overflowing led by dealers, endeavors made by individuals from the Bhabinkamtibnas in forestalling the dissemination of liquor in the legitimate zone of ​​the Tasikmalaya police headquarters were by directing police exercises through advising, sambang and furthermore center gathering conversation. (FGD). In any case, in its execution, this has not yet arrived at its most extreme outcomes, this can be seen from the quantity of alcohol use numbers that keep on expanding from year to year, even not diminishing by any means. This is brought about by a few elements both inside and outer variables of the individuals from Bhabinkamtibmas itself, with the goal that the aftereffects of the usage of these exercises have not been accomplished without limit.